Retrospective Analysis of patients with Acute Diffuse peritonitis - Khan, Mumtaz (Journal of Postgraduate Medical Institute, 2011)
A personel review of 146 patients operated between 1st 1991 and 31st March 1994 is presented. All these patients underwent laparatomy for acute diffuse peritonitis. The two main causes were: spontaneous and traumatic gut perforations. Povidone Iodine solution and Cepharadine were used for thorough peritoneal toilet. Of the 146 patients 21 died within seven days of admission. Eleven of these 21 had purulent peritonitis secondary to a perforated viscus, 8 had sustained firearm injuries and two had stab wounds. Out of 21 five died to pulmonary embolism, 2 of aspiration pneumonia. three patients developed small bowel fistula; one of these three died while the other two recovered with TNP (total Parenteral Nutrition. Complications occured in 59 cases (morbidity of 4.39%). It is concluded that through peritoneal lavage with antiseptic and antibacterial drugs may reduce mortality and morbidity in patients with acute diffuse peritonitis.